Exploratory analysis of the written press of four Latin American countries on domestic violence in the context of confinement due to COVID-19 from a gender perspective - Rodríguez-Gutiérrez, Ana Lucía (2021)
This article had the general objective of analyzing the approach to domestic violence in the framework of the Psychology and Domestic Violence Module of the University of Costa Rica (UCR), during the pandemic caused by COVID-19, in the written press news from virtual media in the Latin American context, in the period between March to May of the year 2020. The sample consisted of 12 news and 8 press releases, from 4 Latin American countries and 4 governmental and non-governmental organizations, which were chosen under the saturation criterion. As main results it was found that the news and press releases visualize the concern of the organizations that deal with cases of violence and the authorities about the imminent increase in cases of domestic violence and gender violence, also, they make clear the need for new complaint mechanisms and the importance of sensitizing gender issues to the staff of the institutions that deal with cases of violence.